Design, Build and Implementation of The Church Services Katolik Paroki Hati Santa Perawan Maria Tak Bernoda Putussibau Web-Based - Lumban Tobing, Heribertus Christian Agusto; Supatman, Supatman (CV. Publikasi Indonesia, 2024)
This research analyzes and develops web-based church services for parishes Hati Santa Perawan Maria Tak Bernoda at Putussibau, using the Laravel framework and the PHP programming language. The purpose of this study is to improve the accessibility and efficiency of information and administrative services in the parish. The research methods used include observation, interviews, system interface design, and implementation evaluation. The result of this research is a parish website that provides various important information such as church profiles, mass schedules, sacrament services, and church contacts, which can be accessed by all parishioners and the general public. This website is expected to support the modernization of church services and make it easier for people to access church information and services. The study also provides recommendations for further development and integration of additional features that can enrich the functionality and benefits of the parish website.